THE ANALYSIS OF THE PRICE COMMODITY INFLUENCING INFLATION IN BALIKPAPAN IN THE PERIOD 2008-2012 - Riskita, Mutia Ayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Using multiple linear regression analysis data from January 2008 to December 2012, this research aimsÂ to analyze of the factors influencing inflation in Balikpapan. The variables used are: Price of Cement, Price of Chili, Price of Onion and Price of Fuel. TÂ -test, F-test and classical assumption are also used in this study to determine the effect of independent variable on dependent variable and also to strengthen the result obtained from multiple regression analysis.Â The finding shows that Price of Cement, Price of Chili, Price of Onion and Price of fuel have a positive and significant influence on inflation. The most influential variable to inflation is Cement. Keywords: Inflation, Price of Cement, Price Onion, Price Chili, Price of Fuel